Nutrient fertilization by dogs in peri‐urban ecosystems. Issue 1 (6th February 2022) - De Frenne, Pieter; Cougnon, Mathias; Janssens, Geert P. J.; Vangansbeke, Pieter
Abstract: (Semi‐)natural ecosystems provide many important benefits to nature and people, but are often located near populated and urbanized areas across the globe. During recreational activities, many people bring dogs into peri‐urban forests and nature, but their nutrient inputs per unit space and time via dog faeces and urine into ecosystems remain scarcely quantified. Here, we estimate net fertilization rates of dogs in peri‐urban ecosystems, with a focus on nitrogen (N) and phosphorus (P) because of their evident effects on plant biodiversity. We used 487 direct‐count censuses over 1.5 years to collect accurate dog abundance data per hectare per year in four sites in peri‐urban forests and nature reserves in Belgium. Based on estimated dog densities and a systematic literature search of nutrient concentrations in urine and faeces, we calculate N and P fertilization rates from urine and faeces deposits, also propagating uncertainty and variability in these estimates. We find that canine N and P fertilization rates on average amount to 11 kg N (more or less equally from urine and faeces) and 5 kg P (predominantly from faeces) per hectare per year, respectively. These estimated amounts are substantial when compared to atmospheric inputs of N and extractable amounts via traditional nature management (e.g. mowing and hay removal). Our estimated dog N and P fertilization rates in peri‐urban forests and nature are substantial. Such levels of nutrient inputs may considerably influence biodiversity and ecosystem functioning, and co‐determine restoration outcomes. Our results underpin the need for managers and policy makers to more often (i) consider currently neglected nutrient inputs by dogs in management plans and restoration goals, (ii) communicate to dog walkers the role of their dog as 'fertilizer' and highlight the necessity to remove at least canine solid faecal waste, (iii) in sensitive oligotrophic ecosystems with species adapted to nutrient‐poor soils, establish nearby off‐leash dog parks, enforce the use of short leashes and/or apply dog bans such that high dog abundances can be avoided. Abstract : Dogs are an underestimated source of nutrient fertilizer and can bring in 11 kg N and 5 kg P per ha per year. Their impact in sensitive ecosystems with plants adapted to nutrient‐poor conditions can be reduced via specific management actions. The photo displays a nature reserve (Plan de Tuéda) in the Alps, France.